Portfolio construction for today's markets : a practitioner's guide to the essentials of asset allocation - Koesterich, Russ (Petersfield, Hampshire : Harriman House, 2018)
For most of the past 50 years the simplest asset allocation solution was often the best. A balanced portfolio of stocks and bonds provided the investor with good returns. Unfortunately, this approach is not likely to work as well in the future. Interest rates are close to historic lows, equity valuations and bond prices appear stretched, and global economic growth has slowed. Investors need a new asset allocation solution. In 'Portfolio Construction for Today's Markets,' BlackRock Portfolio Manager and investment expert Russ Koesterich addresses this problem by describing the step-by-step approach to building a portfolio consistent with investor goals and suited to today's market environment.
Includes index.
oif 21/01/2020
Loans
Keywords: Asset allocation